New dibenzocyclooctadiene lignans from Kadsura induta with their anti-inflammatory activity. Issue 39 (7th September 2022) - Tai, Bui Huu; Yen, Pham Hai; Hoang, Nguyen Huy; Thanh Huong, Phan Thi; Dung, Nguyen Viet; Van Thanh, Bui; Cuong, Nguyen The; Bang, Ngo Anh; Nhiem, Nguyen Xuan; Van Kiem, Phan
Abstract : Five new dibenzocyclooctadiene lignans isolated from the stems of Kadsura induta . Their anti-inflammatory activities were studied by molecular docking and inhibition of NO production in LPS activated-RAW264.7 cells. Abstract : Five new dibenzocyclooctadiene lignans, named kadsuindutains A–E (1–5 ), and three known ones schizanrin F (6 ), schizanrin O (7 ), and schisantherin J (8 ) were isolated from the stems of Kadsura induta . Their structures were determined by analyses of HR-ESI-MS, NMR, and ECD spectra. Compounds 1–5 contain a 2′, 4′-dioxygenated-2′, 3′-dimethylbutyryl moiety which is rarely reported for dibenzocyclooctadiene lignans. Molecular docking predicted that compounds 1–8 displayed good binding affinity to the active site of iNOS and TNF-α proteins but unstable binding to the active site of COX-2 protein. Additionally, in vitro experiments showed that compounds 1–8 inhibited NO production in LPS-activated RAW264.7 cells with IC50 values from 10.7 μM to 34.0 μM, compared to the positive control L-NMMA (IC50 = 31.2 μM).